2019
DOI: 10.1101/722066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validating the Cyc2 neutrophilic Fe oxidation pathway using meta-omics of Zetaproteobacteria iron mats at marine hydrothermal vents

Abstract: 27 Zetaproteobacteria create extensive iron (Fe) oxide mats at marine hydrothermal vents, making 28 them an ideal model for microbial Fe oxidation at circumneutral pH. Comparison of neutrophilic 29 Fe-oxidizer isolate genomes has revealed a hypothetical Fe oxidation pathway, featuring a 30 homolog of the Fe oxidase Cyc2 from Acidithiobacillus ferrooxidans. However, Cyc2 function is 31 not well verified in neutrophilic Fe-oxidizers, particularly in Fe-oxidizing environments. Toward 32 this, we analyzed genomes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…This process, termed extracellular electron transfer (EET), was originally recognized in dissimilatory Fe(III)-reducing organisms (32), but has subsequently been shown to be utilized by FeOB (33,34). Homologs to the Cyc2-type EET system have been found to be present in a broad range of FeOB genomes, including those of aerobic neutrophilic FeOB (33,35), and recently validated via metaomics (36). Organisms of the genera Ralstonia and Rhodopseudomonas which are known to harbor FeOB (37,38) were among the top 10 genera in the enrichment culture based on read classification (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process, termed extracellular electron transfer (EET), was originally recognized in dissimilatory Fe(III)-reducing organisms (32), but has subsequently been shown to be utilized by FeOB (33,34). Homologs to the Cyc2-type EET system have been found to be present in a broad range of FeOB genomes, including those of aerobic neutrophilic FeOB (33,35), and recently validated via metaomics (36). Organisms of the genera Ralstonia and Rhodopseudomonas which are known to harbor FeOB (37,38) were among the top 10 genera in the enrichment culture based on read classification (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FeGenie demonstrates the potential for iron oxidation and reduction in environments that are rich in reduced iron, including the Rifle Aquifer (Jewell et al, 2016), Jinata Hot Springs (Ward, 2017;Ward et al, 2019), and iron mats found at the Loihi Seamount, Mid-Atlantic Ridge, and Mariana Backarc hydrothermal vent (McAllister et al, 2019). FeGenie also demonstrates the potential for these metabolisms to occur in other environments, including the Amazon river plume (Satinsky et al, 2017) and in the open ocean (Tully et al, 2018) (Figure 5A).…”
Section: Case Study: Iron Redox and Acquisition In Diverse Environmenmentioning
confidence: 95%
“…For determination of iron oxidation potential, we included the candidate iron oxidase from acidophilic and neutrophilic iron-oxidizing bacteria, Cyc2 (Barco et al, 2015). As shown by McAllister et al (2019), Cyc2 is represented by three phylogenetically distinct clusters; thus, we constructed three different HMMs, specific to each cluster. Cluster 1 includes sequences from most known, well-established neutrophilic ironoxidizers but is yet to be genetically or biochemically verified as an iron oxidase.…”
Section: Hmm Development: Iron Oxidation/reductionmentioning
confidence: 99%
See 2 more Smart Citations